Connecting the Dots : Selective Fragment Recovery in ICNLoWPAN - Martine S. Lenders and Cenk Gündogan and Thomas C. Schmidt and Matthias Wählisch (Association for Computing Machinery, 2020)
In this paper, we analyze the benefits of integrating 6LoWPAN Selective Fragment Recovery (SFR) in ICNLoWPAN. We present a solution that allows for immediate fragment forwarding - -a key feature of SFR - -in combination with ICN caching. Our proposal introduces a Virtual Reassembling Endpoint (VREP), which acts transparently as an SFR fragment forwarder while simultaneously collecting fragments. Once a datagram is complete, it is exposed to the content cache, effectively making the VREP the new fragmenting endpoint. Our solution complies with current specs defined in the IETF/IRTF. Furthermore, we combine the reverse path forwarding schemes of both SFR and ICNLoWPAN and assess drawbacks and benefits in a testbed. Our evaluation shows that SFR with VREP performs similar to hop-wise reassembly, details depend on the topology, but both outperform SFR without VREP in all scenarios.
Keywords: fragmentation; protocol design; Internet of Things; Information-centric networking; measurement; protocol evaluation; wireless